Accelerating Branding and Digital Transformation of MSMEs Through Digitalisation and Branding Assistance at CV. Nova Tritama - Arfa, Daghastaniy Fairuzza; Hakim, M. Luqmanul; Sharf, Oely Maqwa; Rahmawati, Itsnaini; Aini, Risa Nur (Indonesian Journal of Cultural and Community Development, 2023)
Digital transformation has become a primary need for Micro, Small, and Medium Enterprises (MSMEs) in facing the challenges of a competitive modern industry. Unfortunately, not all MSME players have the understanding and skills to optimally utilise digitalisation and branding strategies. This study aims to describe the digitalisation and branding assistance process carried out at CV. Nofa Tritama as one of the local MSMEs in Bojonegoro Regency. The activities were conducted through interactive training, participatory discussions, and hands-on practice in designing visual identities and digital promotion strategies. The results of the activities showed an increase in the understanding and readiness of SMEs in implementing branding and digitalisation. This study is expected to contribute positively to the development of SMEs' capacity in the digital era.